2012
DOI: 10.5539/elt.v5n4p2
|View full text |Cite
|
Sign up to set email alerts
|

Output and English as a Second Language Pragmatic Development: The Effectiveness of Output-focused Video-based Instruction

Abstract: Swain's Output Hypothesis proposes a facilitative effect for output on the acquisition of second language morphosyntax. In the context of classroom instruction, a number of studies and reviews suggest that explicit instruction in pragmatic elements promotes development. Other studies have offered less conclusive evidence of the effectiveness of various instructional options. The present classroom-based study examined the effectiveness of output-focused, video-based instruction for the development of second lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…When using pragmatic skills as an outcome measure, it is recommended that assessments allow for documentation across various contexts and communication partners (Gerber et al, 2012 ; Norbury, 2014 ). The DCTs were designed by the researcher based on research studies that made use of DCTs (Archer, Aijmer & Wichmann, 2012 ; Chen & Rau, 2013 ; Jernigan, 2007 ; Kasper & Dahl, 1991 ; Kasper & Roever, 2005 ; Martínez-Flor & Uso-Juan, 2011 ). The situations presented in the tasks all included the following information: The setting, social distance and social status (Alemi, Rasekh & Razanjad, 2014 ; Aufa, 2014 ; Chen & Rua, 2013 ; Kasper & Roever, 2005 ; Martínez-Flor & Uso-Juan, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…When using pragmatic skills as an outcome measure, it is recommended that assessments allow for documentation across various contexts and communication partners (Gerber et al, 2012 ; Norbury, 2014 ). The DCTs were designed by the researcher based on research studies that made use of DCTs (Archer, Aijmer & Wichmann, 2012 ; Chen & Rau, 2013 ; Jernigan, 2007 ; Kasper & Dahl, 1991 ; Kasper & Roever, 2005 ; Martínez-Flor & Uso-Juan, 2011 ). The situations presented in the tasks all included the following information: The setting, social distance and social status (Alemi, Rasekh & Razanjad, 2014 ; Aufa, 2014 ; Chen & Rua, 2013 ; Kasper & Roever, 2005 ; Martínez-Flor & Uso-Juan, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…She revealed that computer mediation, which develops instructional materials, had potential contributions to provide opportunities for learners to raise their pragmatic awareness. In the same line, Jernigan (2012) examined the effectiveness of one of instructional options, which is output-focused video-based instruction for EFL learners' pragmatic development. More specifically, he compared the effect of output-focused video-based instruction and comprehension-focused instruction on learners' perception of pragmatic appropriateness and production in written language.…”
Section: Explicit Pragmatic Instructionmentioning
confidence: 99%
“…With the recognition of the significance of speech acts, plenty of techniques for teaching and learning them have come out. Most of the techniques and strategies to the teachability of pragmatic components particularly on the part of speech acts have mainly accounted for the relative effectiveness of different types of pragmatic instruction/mediations or the priority of two approaches of explicit and implicit instruction over one another (Ajabshir, 2019;Derakhshan & Arabmofrad, 2018;Derakhshan & Zangoei, 2014;Emadi, 2015;Hashemi Shahraki, Ketabi, & Barati, 2015;Jernigan, 2012;Kargar, Sadighi, & Ahmadi, 2012;Rose, 2005;Sykes, 2018;Taguchi, Xiao, & Li, 2016;Tateyama, 2001).…”
Section: Introductionmentioning
confidence: 99%